GIS as a tool for Classification Lake’s acidification- and eutrophication degree - Hameed, H.A. (Mesopotamian Journal of Marine Sciences, 2022)
GIS (Geographic information system) was used as a tool to classify 50 lakes according to acidification- and eutrophication degrees. Both water pH and alkalinity showed similar trends of distribution whether they were used alone or together as determining criteria for acidification degree. Where as variables that was used for the determination of eutrophication degree revealed more or less different patterns. Therefore, one must be careful in determining which variable or variables that could be used in classification of lakes according to their eutrophication degree. Moreover, GIS can be used in documentation, analyzing, and prediction the possible future changes in Iraqi aquatic ecosystems.